1997
DOI: 10.1097/00001648-199705000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution from Truck Traffic and Lung Function in Children Living near Motorways

Abstract: The contribution of motorized traffic to air pollution is widely recognized, but relatively few studies have looked at the respiratory health status of subjects living near busy roads. We studied children in six areas located near major motorways in the Netherlands. We measured lung function in the children, and we assessed their exposure to traffic-related air pollution using separate traffic counts for automobiles and trucks. We also measured air pollution in the children's schools. Lung function was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
352
1
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 564 publications
(375 citation statements)
references
References 31 publications
13
352
1
9
Order By: Relevance
“…In the Netherlands, cough, wheeze, runny nose, and doctor-diagnosed asthma were significantly increased for children living within 100 m of the freeway (van Vliet et al, 2000). Another report from the Netherlands indicates that exposure to traffic-related air pollution, in particular diesel exhaust particles, may lead to reduced lung function in children living near major motorways (Brunekreef et al, 1997). In Munich, adolescents who self-reported constant truck traffic exposure had increased prevalence odds ratio of 2.15 for wheezing (Duhme et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Netherlands, cough, wheeze, runny nose, and doctor-diagnosed asthma were significantly increased for children living within 100 m of the freeway (van Vliet et al, 2000). Another report from the Netherlands indicates that exposure to traffic-related air pollution, in particular diesel exhaust particles, may lead to reduced lung function in children living near major motorways (Brunekreef et al, 1997). In Munich, adolescents who self-reported constant truck traffic exposure had increased prevalence odds ratio of 2.15 for wheezing (Duhme et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The approximate length of one city block in Anchorage is 100 m. Anchorage Air Quality Section studies have shown that PM 10 measured at 10 ft (3 m) from the road declined by 50% at 165 ft (50 m) from the road. Increased respiratory symptoms have been detected at distances up to 300 m from major roads (Brunekreef et al, 1997), and an additional traffic variable based on a 300-m buffer was also calculated. All the road segments that fell within the 100-m buffer were multiplied by the traffic count of that road at that point and then summed to create a measure of traffic exposure; this method allowed for weighting the effect of major roads by their proximity.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Several toxicological and epidemiological studies have confirmed the relationship of exposure of particles to human health (Brunekreef et al, 1997;Dockery et al, 1993;Saxon and Diaz-Sanchez, 2000;Schwartz et al, 1996). There are several studies that have also indicated the cofounding effects of anthropogenic aerosols (such as industrial emissions, traffic exhausts) and naturally occurring bioaerosols in respiratory disorders (Nel et al, 1998;Takenaka et al, 1995).…”
Section: Introductionmentioning
confidence: 94%
“…Some studies have found an association between traffic volume and the number of hospital admissions for asthma (English et al, 1999), vehicle or truck traffic and self-reported symptoms of asthma (Weiland et al, 1994;Duhme et al, 1996), but others have found no association between asthma and traffic volume (Wilkinson et al, 1999). Truck and road traffic were related to chronic respiratory symptoms and reduced lung function in studies of adolescents (Wjst et al, 1993;Oosterlee et al, 1996;Van Vliet et al, 1997;Brunekreef et al, 1997;Ciccone et al, 1998). Most of these studies used traffic counts as a surrogate for exposure to vehicle emissions.…”
Section: Introductionmentioning
confidence: 99%